Recent advances in exploring the properties and applications of hyaluronan - Qingkai Zeng; Dahai Ding; Ravi Sankar Loka; Shuaishuai Wang; Peixue Ling (Journal of Dermatologic Science and Cosmetic Technology)
Hyaluronan (HA) is a naturally occurring polysaccharide in the organism. As one of the main components of the extracellular matrix, it plays an important role in regulating various cellular processes, including proliferation, differentiation, inflammation, and immunity, through interaction with HA receptors. HA is widely found in the human body, particularly in the skin and joints, thus playing a crucial role in the functioning of these tissues. The aging of the skin and the occurrence of osteoarthritis are related to the loss of HA. Supplementing HA in the appropriate areas can delay or prevent these processes. Common methods of HA supplementation include topical application to the skin or injection into the joint cavities, both of which have shown efficacy in restoring HA levels and improving tissue function. In recent years, studies have shown that oral administration of HA can also have similar effects. Oral HA first passes through the gastrointestinal tract and then enters the liver with the blood circulation. Therefore, in addition to supplementing the HA content in the body, oral HA can also exert beneficial effects on the gastrointestinal tract and the liver, such as enhancing the barrier function of the gastrointestinal tract, regulating the intestinal flora, and reducing inflammation. Supplementation of HA has numerous benefits for the skin, orthopedic disorders, gastrointestinal tract and liver. Therefore, it is important to understand the mechanisms through which HA exerts these effects. This article describes the basic properties of HA and reviews its relationship with skin, orthopedic diseases, gastrointestinal tract and liver, as well as its applications in these areas.